High-Dose or Low-Dose Aspirin Application in the Initial Phase of Kawasaki Disease: A Meta-Analysis and Systematic Review. (14th October 2022) - Liu, Kun; Wang, Lu; Gong, Linxia
Abstract : The initial dose of aspirin for Kawasaki disease (KD) is controversial to a great extent. In order to compare the efficacy of high-dose and low-dose aspirin in the treatment of KD, this study included articles containing information on the treatment of KD with aspirin before August 2021, which were collected from public databases. The results of different studies were summarized and weighted by an inverse variance model, and heterogeneity was assessed using the Q-test and I 2 . A meta-analysis of 12258 patients from nine retrospective studies was conducted. In general, no significant differences between high-dose and low-dose groups were found in the incidence of coronary artery abnormality (CAA) (RR = 1.154; 95% CI = 1.027–1.316) and the incidence of intravenous immunoglobulin (RR = 0.926; 95% CI = 0.594–1.441). But high-dose aspirin might be linked to the shortened duration of fever (RR = −0.134; 95% CI = −0.203–0.064) as well as hospitalized stay (RR = −1.263; 95% CI = −1.392–1.122). Conclusion . For the treatment of the acute phase of KD, low-dose aspirin plus intravenous immunoglobulin could be as effective as high-dose aspirin in preventing CAA. Nonetheless, high-dose aspirin might be related to reducing fever time and hospitalization time.